Pengimplementasian Peningkatan Status Gizi Balita Melalui Pemberdayaan Keluarga Dalam Pencegahan Stunting Di Nagari Pariangan Kabupaten Tanah Datar Provinsi Sumatera Barat - Indah Santia; Rahmadani Yusran; Muhammad Farid Surya; Naufal Al Haady (Pusat Riset dan Inovasi Nasional, 2023)
Stunting by age (short) is height less than minus two standard deviations (<-2SD) based on the WHO Child Growth Standard Nutritional Status Chart. Stunting can be a major threat to the quality of Indonesia's population and its competitiveness. Factors that must be met to implement a balanced nutritional diet include adequacy of quantity and quality, diverse nutritional content in daily life, and the ability to store nutrients to meet the needs of the body. Studies have shown that stunting interferes with children's physical development, causing brain development to be suboptimal at its peak. Research also shows that stunting in Indonesia, especially in Nagari Pariangan, Tanah Datar Regency, interferes with children's social and emotional development. The causes of stunting are divided into two categories, namely biological causes and environmental causes. The application of a balanced nutrition diet emphasizes food consumption patterns in terms of variety and quantity, following the principle of food diversity to prevent nutritional problems. Factors that must be met in applying a balanced diet include the adequacy of quantity, quality, and content of various nutrients in daily life. This research was conducted to further examine how to improve the nutritional status of toddlers through family empowerment in preventing stunting in Nagari Pariangan, Tanah Datar district, West Sumatra province. The researcher used qualitative analysis techniques to observe how the implementation of improving toddler nutrition through family empowerment in preventing stunting through outreach activities on understanding stunting and directly went to the field to collect data on families who have children aged 0-5 years in Nagari Pariangan, Tanah Datar Regency, West Sumatra Province